Conservation of helical bundle structure between the exocyst subunits - Croteau, Nicole; Devos, Damien (PLOS ONE, 2009)
Background The exocyst is a large hetero-octomeric protein complex required for regulating the targeting and fusion of secretory vesicles to the plasma membrane in eukaryotic cells. Although the sequence identity between the eight different exocyst subunits is less than 10%, structures of domains of four of the subunits revealed a similar helical bundle topology. Characterization of several of these subunits has been hindered by lack of soluble protein for biochemical and structural studies. Methodology/Principal Findings Using advanced hidden Markov models combined with secondary structure predictions, we detect significant sequence similarity between each of the exocyst subunits, indicating that they all contain helical bundle structures. We corroborate these remote homology predictions by identifying and purifying a predicted domain of yeast Sec10p, a previously insoluble exocyst subunit. This domain is soluble and folded with approximately 60% α-helicity, in agreement with our predictions, and capable of interacting with several known Sec10p binding partners. Conclusions/Significance Although all eight of the exocyst subunits had been suggested to be composed of similar helical bundles, this has now been validated by our hidden Markov model structure predictions. In addition, these predictions identified protein domains within the exocyst subunits, resulting in creation and characterization of a soluble, folded domain of Sec10p.